UPAYA PENINGKATAN KESADARAN LINGKUNGAN GUNA MENUNJANG PENINGKATAN PENDAPATAN MASYARAKAT - Yosi Eka Putri; Nisha Selvia; Erita Erita (Universitas PGRI Sumatera Barat, 2024)
Rapid population growth has pushed the volume of waste to increase due to increased public consumption. The management of household waste by the community is still relatively low. This phenomenon is also seen in the Griya Pesona Housing in Padang City. The results of preliminary observations and interviews show that there is still a low level of public awareness to dispose of waste in official waste disposal sites and the low role of the community in supporting government programs related to household waste management. This study aims to build public awareness and concern in the Griya Pesona Housing City of Padang in managing household waste. Environmental communication is carried out using mass communication in the form of banners and personal communication in the form of door to door counseling by distributing brochures. The results of this study indicate that there is an increase in citizen awareness about household waste management where there is a change in attitude, knowledge and behavior after education is carried out by implementing mass and personal communication strategies. Behavior change through personal communication is more influential than mass communication. Mass communication can be used to increase knowledge, but behavior change is more influential when personal communication is used. In addition, the community has also begun to realize the importance of maintaining cleanliness and managing household waste, such as separating waste by type and disposing of waste in official disposal sites.Keywords: communication strategy, environment, community awareness, waste management